Mannequin-Based Immersive Simulation Improves Resident Understanding of a Clinical Decision Rule. (October 2017) - Harwayne-Gidansky, Ilana; Bellis, Jennifer M.; McLaren, Son H.; Critelli, Kristen; Clark, Sunday; Chen, Zhengming; Gerber, Linda M.; Ching, Kevin
Objective. Simulation-based medical education may aid to standardizeclinical performance measures, though there is little evidence for using an immersive, mannequin-basedsimulation for knowledge acquisition . We predicted that residents who had participated in an immersive simulation exercise illustrating the use of a clinical decision rule plus routine instructional methods (experimental group) would understand and implement this tool better than interns who participated in animmersive simulation focused on traumatic brain injury with intracranial hypertension plus routine instructional methods (control group 1). We further predicted that interns in the experimental group would understand and implement this tool as well as senior residents with more clinical experience (control group 2). Methods. This was a single center, prospective, simulation-based, randomized controlled trial.Pediatric interns were randomly assigned toclinically integrated teaching, plus a single, immersive simulation and structured debrief aimed at teaching this tool in minor head trauma (intervention), orclinically integrated teaching plus a related simulation on intracranial hypertension. Senior residents were used as an historical control arm and did not participate in a simulated encounter. Results. 20 interns (ten per group) participated in the study. Senior residents (n=40) served as historical comparisons. Interns in the intervention group scored similar to senior residents on astructured clinical observation score (median 64% vs. 57%), and better than interns in the placebo group (median 64% vs. 43%). Conclusions. In this study, a singleimmersive simulation improved resident learning and application of a clinical prediction rule when compared to standardresident education .